Bridging Global Knowledge : Educating Communities on International Trade Principles - Rangkuty, Dewi Mahrani; Suryani Sajar; Rahmadhani Fitri; Naibaho, Yanti Br (International Journal of Economics, Management and Accounting, 2024)
The purpose of this service is to educate the Concept of Waste Bank, Green Economy, and Money Supply to the Community in Medan Belawan District. The special target in this community service is for the workers of the Blessing Waste Bank in Medan Belawan District to know what the Waste Bank, Green Economy, and Money Supply to the Community in Medan Belawan District is, how its application is an opportunity for household income, for example by becoming a new source of income from saving household waste that has been implemented so that they are able to read the economic and environmental problems that occur. The material presented at this community service is: what is a Waste Bank, Green Economy, and Money Supply, how the impact of the Waste Bank on income from household waste. Which can improve household welfare through public knowledge/understanding related to Waste Banks, Green Economy, and Money Supply. From this community service, it shows the results that with the existence of the Waste Bank, the application of the Green Economy concept can be seen from the collection of household waste that is easily collected at the Waste Bank, the community becomes a customer, has savings, withdraws money, then continues to spend consumption from the money which means that there are selling and buying activities in the market because of the money circulating in the community. This affects economic activities in the Medan Belawan District area.